Urban Sophie Iron Board / Ira Wahadah Md Ghazali - Md Ghazali, Ira Wahadah (2020)
By revising the feasibility study, we have determined several business problems that relates to the company. If there are no action taken to prevent these problems, they might affect the efficiency of business operations. The first main problem is the existing iron board does not come with mirror on its back. This result to customer needs to buy two separated items to fulfil their desired. Plus, since the company’s target market are single working person, usually a single person’s house is not to big. By buying two separated items of iron board and mirror, will cause the house look cramped. The next problem which arises is the most existing iron board are made of non-quality materials. They are easily to break if not handle with care. The screws often fall off if the iron board are fold frequently resulting to inconvenience to customers. Not to mentioned, existing iron board too does not come with advanced technology such as adjustable rotation or rotation lock which make it hard for customer to adjust the suitable position they wanted.